The effect of elevated temperature on properties of mortar containing crushed cockle shell and palm oil fuel ash as mixing ingredient - Mohamad Firdaus, Mohamad Azhar (2016)
The issues on increasing utilization of waste materials from industry such as palm oil fuel ash and cockle shell during concrete production to meet the continuous demand of the construction industry has led towards efforts of using any waste material as partial replacement in this composite material. Nowadays, sand has become the most widely consumed natural resources on the planet after fresh water. By using POFA and cockle shell effectively, it can reduce the bad environmental effect, and it can also solve the landfill problem for the disposal of waste and sand mining activities. This thesis is to study the effect of elevated temperature on properties of mortar containing crushed cockle shell and palm oil fuel ash as mixing ingredient. The mortar subjected to the experiment consist of 20% of the crushed cockle shell and 20% of palm oil fuel ash that has been sieved as a partial sand replacement and cement sand replacement. The size of the mortar used is 50x50x50 mm (length x width x height). The specimens were water cured for 7, 14 and 28 days. The specimens were subjected to compressive strength test, acid resistance test and elevated temperature test. The results show that plain cement mortar (C) exhibits better resistance towards acid attacks. Besides, for elevated temperature test, the mix with 20% of cockle shell (CCS) exhibit longest percentage of mass loss compared to the other mix. Also, the mix with the 20% of cockle shell (CCS) shows the highest value of compressive strength rather than the other mix.